2002
DOI: 10.1099/00221287-148-12-3913
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycobacterium tuberculosis ribosome recycling factor (RRF) and a mutant lacking six amino acids from the C-terminal end reveals that the C-terminal residues are important for its occupancy on the ribosome

Abstract: Ribosome recycling factor (RRF), coded for by the frr locus, is involved in the disassembly of post-termination complexes and recycling of the ribosomes for a fresh round of initiation in bacteria and in eukaryotic organelles. In a crossspecies-complementation experiment, it was shown that the Thermus thermophilus RRF protein lacking five amino acids from its C-terminal end (∆C5TthRRF) but not the full-length protein (TthRRF) complemented Escherichia coli for its frr ts phenotype. It was also shown that the My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Again, the rRNA residues in the close neighborhoods of these contacts are modified bases, methyl-U1939 and methyl-C1962. Observation of an interaction of RRF, involving its C terminus, is consistent with genetic studies (31,32) showing that this region of RRF is important for its occupancy on the ribosome.…”
Section: Comparison Of Atomic Structures Of Rrf With Corresponding Crsupporting
confidence: 69%
“…Again, the rRNA residues in the close neighborhoods of these contacts are modified bases, methyl-U1939 and methyl-C1962. Observation of an interaction of RRF, involving its C terminus, is consistent with genetic studies (31,32) showing that this region of RRF is important for its occupancy on the ribosome.…”
Section: Comparison Of Atomic Structures Of Rrf With Corresponding Crsupporting
confidence: 69%
“…11,18 Significant studies have been carried out on MtRRF, the RRF from the pathogen Mycobacterium tuberculosis. 2,19 Interestingly, these studies have demonstrated MtRRF to possess certain properties different from the two widely studied RRFs, EcRRF and TtRRF. Cross-species complementation experiments show that MtRRF completely fails to function in E. coli, 2 while TtRRF shows residual function.…”
Section: Introductionmentioning
confidence: 97%
“…30 MsmRRF, MtuIF3, and His 6 -MtuEFG from pET14bMtuEFG, and MsmEFG from pRSETBMsmEFG were purified as described in Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%